The use of ICT in hospitals: a Portuguese backstage analysis - Mendes, Rita (29th Patients Classifications Systems International (PCSI), 2013)
Introduction: Nowadays, information systems are essential to all areas of health care. From international comparability, to data mining or to benchmarking is unquestionable the importance of rise up a memory reporting system. ICT allows simultaneously increase the productivity and the quality of services provided at lower cost. Several studies recognized that the nucleus part of the information systems (in)success depends more of the human, organizational and cultural factors than of technologies improvement (IOM, 2008; Herzlinger, 2006; Porter, 2006, Ammenwerth, 2006). Beyond mere technological solutions, ICT represents changing processes that require a detailed analysis. Only this knowledge will allow quality and reliable records. As key-actors, how health professionals use the ICT in their activity? How they perceive the ICT use and implementation? The ICT decision came from whom? Methods: This abstract presents the main results of a PhD thesis about the ICT use in Portuguese health sector. This project was developed at 3 levels: political orientation, trend practices and perceptions. This paper will focus on the last two: the meso and the micro level. At the meso level, the ICT use was analyzed through a survey applied biennially (since 2004) by the national institute of statistics that produce information about ICT hospitals equipment (computers and peripherals), about the hospital Internet’s presence, identify the areas were ICT are used most and know more about ICT availability for inpatients, among other ICT issues. At the micro level, to understand usefulness and implementation of ICT process were interviewed 76 health professionals (physicians, nurses, administrative staff, health managers, and hospitals board) in 6 hospitals, and developed 7 case-studies : Hospital Pulido Valente (currently CHLN–North Lisbon Hospital Centre) with the medicine circuit and computerized patients’ management; the Portuguese Oncology Institute of Lisbon, with intranet and institutional website; Hospital Pedro Maria Grande (currently ULSNA –Local Health Unit of North of Alentejo) with electronic prescription; Hospital Infante D. Pedro with Telematic Health Network, the ULS Matosinhos (Local Health Unit of Matosinhos) with integration of hospital and primary units clinical and administrative data (using SONHO, SINUS, SAM and SAPE applications) and Hospital da Arrábida with RisPacs project, an application that scanned part of the radiology department. Results: The meso analysis main results’ can be systemized in 7 ideas: 1) Despite the increasing trend, the computer’s number from 2004 to 2008, when compared with the users, shows a lack of computerized workplaces. 2) Similar trend was found within computers with internet access. 3 The ICT applications more used in hospitals are the anti-virus, e-mail. 4 The hospital back office services are the most ICT users, especially the financial and administrative management, human’s resources management, stock management, (pharmaceutical stocks). 5 From 2004 to 2008, the capacity and speed of internet access increased (via xDSL or RIS). 6 Following the increasing trend of ICT use, the telemedicine practice, from 17% in 2004, increased to 71% in 2008. 7 The institutional sites are made mainly by external companies. At the micro level, the 7 main conclusions are: 1) Lack of communication within organization workers (especially vertical); 2) The ICT professionals use and adoption is deeply related with the recognition of add value and professional performance improvement 3) The professional’s lack of trust in ICT is mainly caused by network errors (inability of the network in several locations in Portugal), discontinued experiences, applications usefulness, these factors increase professional’s resistance. 4) Physicians are the most resistant professional group to ICT use, especially the elderly. Hospital’s physicians are more resistant than the primary care ones that recognize high utility levels and showed lower resistance to ICT changes. 5) Nurses, as a professional group, showed a more proactive adoption of ICT. 6) Computer departments are identified with a lower responsiveness capacity to informatics’ problems. 7) The ICT acquisition is made without needs assessment or inclusion of professionals who will use it. Conclusions: This project found “island-hospitals” and recognized the need to develop a national knowledge and strategy to ICT health sector, supported by a network care conception (national past experience). It's also need to build a powerful and reliable technical network. It highlighted the need of decision-makers being accountable for ICT options and applications earnings in each institution; and the importance of include a ICT approach in health professionals curricula to discuss existing solutions,the importance of standardize concepts and the potential of ICT in professional practice.